2013
DOI: 10.1039/c3ob41353e
|View full text |Cite
|
Sign up to set email alerts
|

Single-step syntheses of no-carrier-added functionalized [18F]fluoroarenes as labeling synthons from diaryliodonium salts

Abstract: Radiotracers labelled with short-lived fluorine-18 (t1/2 = 109.7 min) are keenly sought for biomedical imaging with positron emission tomography (PET). The radiotracers are mostly required at high specific radioactivities, necessitating their radiosyntheses from cyclotron-produced no-carrier-added [18F]fluoride ion. PET radiotracers encompass wide structural diversity and molecular weight. Hence, diverse 18F-labeling methodology is needed to accomplish the required radiosyntheses in a simple and rapid manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…4,11,13,15,20 Exceptionally, oxidation of 1-iodo-4-(trifluoromethyl)benzene by peracetic acid gave not the (diacetoxyiodo)arene but the bridged compound μ-oxa-bis[(acetoxyiodo)-4-trifluoromethylbenzene] ( 1s; structure shown in Supporting Information), as characterized by NMR and MS data (see Experimental). Such bridged compounds may arise from hydrolysis of the corresponding (diacetoxyiodo)arenes when they bear a strong electron-withdrawing group.…”
mentioning
confidence: 99%
“…4,11,13,15,20 Exceptionally, oxidation of 1-iodo-4-(trifluoromethyl)benzene by peracetic acid gave not the (diacetoxyiodo)arene but the bridged compound μ-oxa-bis[(acetoxyiodo)-4-trifluoromethylbenzene] ( 1s; structure shown in Supporting Information), as characterized by NMR and MS data (see Experimental). Such bridged compounds may arise from hydrolysis of the corresponding (diacetoxyiodo)arenes when they bear a strong electron-withdrawing group.…”
mentioning
confidence: 99%
“…As a formal anion, tosylate or another organic anion is often preferred over halide to confer good solubility of the salt in the organic solvent to be used for radiofluorination (eg, dimethylformamide [DMF] and acetonitrile [MeCN]). Simple metathesis reactions can be used to replace the anion with the one that is desired . Nonetheless, halide anions have sometimes been found preferable for high radiofluorination yields.…”
Section: Discussionmentioning
confidence: 99%
“…The same research group has demonstrated high radiochemical conversion using the pyridine derivative by halogen (Cl) exchange . More challenging fluorine‐18 labelings at the meta‐position to prepare 3‐[ 18 F]fluorobenzaldehydes have also been reported by our and other groups from a variety of precursors . Recently, Richarz et al reported fluorine‐18 labeled benzaldehydes according to the “minimalist” radiolabeling protocol, without base and azeotropic drying of [ 18 F]fluoride .…”
Section: Introductionmentioning
confidence: 97%